Hubungan Pola Asuh Orang Tua Dengan Keberhasilan Toilet Training Pada Anak Usia Toddler - Ratne Ratne; Heni Purwaningsih; Raharjo Apriatmoko (Universitas Ngudi Waluyo, 2019)
Toddler are the most important age in toilet training exercises.Toilet training is an attempt to train children to be able to control tourinate or defecate. Succesful toilet training is not only affected bythe ability of the physical, psychological , and emotional of thechildren themselves but also by parenting patern applied to childrenThis study aims to determine the correlation between successfultoilet training to toddler in Nyatnyono village West Ungaran,Semarang regency.This studyused quantitative research usingdescriptive analytic method. The samples in this study were 70respondents using simple random sampling technique. Statisticaltest used chi square with α = 0.05.This study showed that the majority of the parents applied receptiveparenting as many as 33 respondents ( 47.1 % ) with successfultoilet training as many as 20 respondents ( 60.6 % )Based on the analysis of data obtains the significant value ofp=0.007<α ( 0.05 ) which means that there is a correlation betweensuccessful toilet training to toddler in Nyatnyono village WestUngaran, Semarang regency